2017
DOI: 10.1016/j.jceh.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C: Do Generics Work as Well as Branded Drugs?

Abstract: India has a large share of the hepatitis C virus (HCV) burden of the world. Unsafe medical practices and blood transfusions are the leading modes of transmission of HCV in India. The commonest HCV genotype in India is genotype 3 followed by genotype 1. While directly acting antivirals (DAAs) agents have become available at reasonable rates in India, cost of therapy remains a major barrier for control of HCV in India. Generic DAAs have been proven to be cost-saving in prior studies. We examined data from variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Omar et al (2018) showed that among 18,378 patients with HCV-G4 treated within the Egyptian national program with generic SOF-DCV, the SVR rate was 95.1%. Similar high SVR rates were presented in other reports for SOF-LDV (Zeng et al, 2017;Gupta et al, 2018), and for SOF-Velpatasvir (Liu et al, 2018), including patients co-infected with HIV (Premkumar et al, 2017). The largest real-life report for treatment of HCV with generic drugs came from the Egyptian national HCV treatment program, where 98.4% of 107,213 patients treated with generic SOF-DCV achieved an SVR (Elsharkawy et al, 2018a).…”
Section: Discussionsupporting
confidence: 77%
“…Omar et al (2018) showed that among 18,378 patients with HCV-G4 treated within the Egyptian national program with generic SOF-DCV, the SVR rate was 95.1%. Similar high SVR rates were presented in other reports for SOF-LDV (Zeng et al, 2017;Gupta et al, 2018), and for SOF-Velpatasvir (Liu et al, 2018), including patients co-infected with HIV (Premkumar et al, 2017). The largest real-life report for treatment of HCV with generic drugs came from the Egyptian national HCV treatment program, where 98.4% of 107,213 patients treated with generic SOF-DCV achieved an SVR (Elsharkawy et al, 2018a).…”
Section: Discussionsupporting
confidence: 77%
“…For instance, the Punjab government launched the “ Mukh Mantri Punjab Hepatitis C Relief Fund (MMPHCRF)” for free universal treatment of HCV patients with DAAs and thus improve access to treatment. This has been possible due to the availability of generic DAAs which have significantly lesser cost as compared to the branded DAAs, at comparable efficacy [11]. The MMPHCRF scheme was launched in 2016 and uses the existing infrastructure of 22 secondary level district hospitals and 3 tertiary level medical colleges in Punjab to deliver HCV infection related treatment and care [12].…”
Section: Introductionmentioning
confidence: 99%
“…The regimen and the duration of treatment will have to be individualised to the region where generics are variably available and cost is a factor. In most countries in Asia, pangenotype generics are available and highly effective . The challenge, as we move forward is in identifying infected patients and treating them effectively while we attempt to reduce the burden of the costs of virologic testing and on treatment and post‐treatment follow‐up evaluation.…”
Section: Discussionmentioning
confidence: 99%